Exploration and Exploitation Strategy for Innovation and Competitive Advantage of Companies - Haikal Muhammad Hikam; Rofiaty; Christin Susilowati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aimed to analyze the exploration and exploitation strategies implemented by one of the largest orchid producers in East Java. The research method employed a qualitative approach using a case study, with data collection techniques including in-depth interviews, observation, and documentation. The data were analyzed using qualitative descriptive techniques through data reduction, presentation, and systematic conclusion drawing based on field findings. The results show that the company’s exploration strategies in the internal aspect include inclusivity, adaptive culture, digital-based financial management, product and process innovation, as well as the implementation of information systems, while external exploration focuses on value and new market creation, empowerment of plasma farmers, differentiation, and the adoption of new technologies. Meanwhile, internal exploitation strategies involve transparency, strengthened control, employee competency improvement, product and process development, and enhancement of information quality, whereas external exploitation is carried out through value and market improvement, collaboration with plasma farmers, product modification, and optimization of existing technologies. In conclusion, the consistent combination of exploration and exploitation strategies strengthens the company’s competitive position while ensuring the business sustainability in the dynamic orchid industry.